Learning in distance education: Perceptions of 4th year Portuguese students - Ferreira, Carlos Alberto (2023)
Due to the Covid-19 pandemic, distance learning began to take place. Hence, a questionnaire was conducted to 4th year of Portuguese school about their perceptions on this form of learning, with regard to technological resources and the types of tasks performed, the help provided to students, the obstacles that have arisen and the positive and negative aspects of distance learning. A qualitative research methodology was followed with the application of a questionnaire with open questions to three classes of that grade in three different schools in the north of Portugal. The results showed that there were several technological tools used for distance learning, both for synchronous classes and for carrying out school tasks. The lack of socialization with classmates, malfunctioning of technological resources, work overload and students' anxiety were the most negative aspects mentioned by them.